1994
DOI: 10.1364/ol.19.000846
|View full text |Cite
|
Sign up to set email alerts
|

Nanosecond single-photon timing with InGaAs/InP photodiodes

Abstract: We demonstrate that separate absorption and multiplication InGaAs/InP avalanche photodiodes can work biased above the breakdown voltage and detect the arrival time of single photons with 1-ns resolution and a noise-equivalent power of 1 x 10(-14) W/Hz((1/2)) at 150 K. We investigated the performance of various samples, cooling the detectors from different temperatures down to 50 K. These devices are suitable for the detection of short optical pulses in the near-infrared range up to a 1.55-microm wavelength, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Photosensitive devices such as photodetectors in long-wavelength optical fiber communication systems [1,2] and high-efficiency solar cells with multi-junction structures [3] are excellent examples of technologies that utilize the superb optical properties of InP-based systems. With the aforementioned devices, however, surface reflection is a serious problem that degrades the device performance because is reduces the efficiency of photon energy conversion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitive devices such as photodetectors in long-wavelength optical fiber communication systems [1,2] and high-efficiency solar cells with multi-junction structures [3] are excellent examples of technologies that utilize the superb optical properties of InP-based systems. With the aforementioned devices, however, surface reflection is a serious problem that degrades the device performance because is reduces the efficiency of photon energy conversion [4].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, extensive investigations have been carried out on germanium and ffl-V APD's. 4 Recently we have demonstrated that germanium APD's cooled at 77K can work in the so-called Geiger-mode, achieving single photon sensitivity with a Noise Equivalent Power (NEP) of 8.10b6 Wi'%JHz at 1.3pm-wavelength and featuring an equivalentbandwidth of 1.8GHz.5…”
Section: Arrays For Single Photon Detection In the Near Infraredmentioning
confidence: 99%
“…Specifically, larger avalanche signals correspond to larger amounts of charge, which populates more traps within the SPAD and increases the afterpulsing [114,146]. Specifically, larger avalanche signals correspond to larger amounts of charge, which populates more traps within the SPAD and increases the afterpulsing [114,146].…”
Section: Introductionmentioning
confidence: 99%